NASAKH DALAM HUKUM ISLAM - Mayangsari R, Galuh Nashrullah Kartika (IAIN Tulungagung, 2016)
In Ulumul Qurâan , the existence of discourse about abrogating (Nasakh) is the real proof that there is a dialectic relationship between revelation and reality. Nasakh is the cancellation of the law. It could be eliminating and releasing the text of the law referring to reading. It also could be defending the text to show the instruction of abrogated law. The research is based on qualitative descriptive study that limits the study on the Mawarits and Wasiyat verses. The paper is expected to provide scientifc contributions in the form of conceptualization of Ulumul Qurâan oriented to legal legislation and to provide intellectual contributions that combine theory of Nasakh in Ulumul Qurâan through a legal context of usul fqh. Therefore, it is also possible to be an alternative development of Philosophy of Islamic Law .Keywords: Nasakh , Legal Legislation, Wasiat, Mawaris.